BRANZI / Andrea Branzi. - Burkhardt, François; Morozzi, Cristina (Paris : Editions Dis Voir, 1994)
“The relations between art and design are not easy to theorize, because they are always spontaneous and discontinuous. At one time art produced new languages and design used them. Today, though, we see artists using languages invented by design, while designers are invited to exhibit at Documenta, and in galleries and museums. It’s clear, then, that this theory of a one-way transfer of languages is obsolete...“ (A. Branzi) At the heart of the debates which over the past twenty years have made design what it is, the work developed by Andrea Branzi stands out as that of a theorician of design, as much in terms of his production, his writing and lecturing.
Engels
boek
Keywords: Branzi, Andrea; Italië